Grammatical Cohesive Devices Errors Found in Senior High School Students’ Narrative Text - Ida Ayu, Regina Cahyani; I Gst. Ayu Gde , Sosiowati; A.A.Sg. , Shanti Sari Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Senior high school involves students to deal with more complex language rules and expressing ideas in a more sophisticated way. Consequently, senior high school students are inevitably prone to errors in their English writing, particularly in the aspect of creating cohesive and coherent text. This study aims at identifying the types and causes of grammatical cohesive devices errors found in the narrative texts written by senior high school students. This study was conducted using descriptive qualitative method. Documentation method utilized by a checklist instrument and note-taking technique were used to collect the data. The method for presenting the data analysis in this study was informal method. In analysing the data, this study employed the theory from Dulay, Burt, and Krashen (1982) to analyse the types of the grammatical cohesive errors and Richards theory (1973) to analyse the causes of the errors. The results show that all types of grammatical cohesive devices errors were found in the texts. The type of the error was dominated by the omission of reference. The interlingual factor caused the omission and misordering of references. The errors caused by intralingual factor including overgeneralization, incomplete application of rules, ignorance of rules restriction, and false concept hypothesized. These instances of errors disrupt the clarity of the text and the readers’ comprehension. Therefore, study's findings reveal that senior high school students face significant challenges in using grammatical cohesive devices effectively in their narrative writing.